DYNAMICS COMMUNITIES OF BACTERIA AND YEAST IN PROCESSING ROBUSTA COFFEE WITH WET PROCESSING: SCREENING OF DOMINANT ISOLATES - Nusaly, Windy Natalia; Pentury, Kresyan (Universitas Pattimura, 2020)
The type of coffee processing has a direct impact on the microbial community it contains and the quality of the coffee it produces. Coffee processing with a wet process (wet) is known to produce coffee with a good aroma and taste profile. This study aims to determine the dynamics of the bacterial and yeast community during the postharvest process and to determine the dominant microbes involved in the processing of Robusta coffee using a wet process. The method used was the isolation of bacteria and yeast using selective medium with the addition of antibiotics, then morphological identification and calculation of the index of diversity (H), dominance (D) and evenness (E) were carried out based on the bacterial and yeast isolates obtained, as well as screening of dominant isolates based on results of dominance analysis and enzymatic activity. The isolation results obtained by the yeast community (51.7%) with a higher number than the bacterial community (48.3%). The microbial community in the wet processing of Robusta coffee had a species diversity index (H') = 2.48, evenness (E) = 0.74 and dominance (D) = 0.17. The results of isolates screening through enzymatic tests showed bacterial isolates B10 and yeast Y2 were selected as dominant isolates and could be used as starter cultures in a controlled fermentation process.